The development of a balanced scorecard for DOST-Caraga's Small Enterprise Technology Upgrading Program (SET-UP) Core Funded Projects - Dejarme, Jennifer Jao (University of the Philippines Diliman, 2012)
The Balanced Scorecard (BSC) is a strategic performance management framework intended to help an organization monitor its performance and manage the execution of its strategy. The concept was originally introduced in 1992 by Robert Kaplan and David Norton in Harvard's Business Review Article. Since then it has been acknowledged as one of the most influential business ideas that has governed organizations in their pursuit for success. A Balanced Scorecard measures organizational performance across four perspectives : financial, customers, internal business process and learning and growth. The financial perspective highlights the cost and ability of an organization to provide the best value to customers and stakeholders. Customers perspective focuses on the firm's overall responsibility to address customers needs in the most efficient and effective manner. The internal business process perspective puts emphasis on performance expectations and in making sure that suitable processes and resources are accessible and applied to maximize performance. The focal point of the learning and growth perspective is on employee's ability and the organizational framework required to attain the agency's goals. Some benefits gained in the use of a balanced scorecard include better strategic planning, communication and execution within an organization. BSC promotes effective strategic and organizational alignment. It can also improve performance reporting and can enhance information management. Although scorecards have convincing benefits, these will only be realized if the implementation process is done whole heartedly and with no shortcuts. The barriers for the effective implementation of the BSC include : the vision of the organization, people, resources and management. On the other hand, success factors can be attributed to the organization's commitment, clarity of objective, effective communication process, accountability, link to strategy and proper reporting. Initially, the BSC was designed for private sector but it has gained advocates from the public and non-profit sectors due to the perceived benefits of the tool. To differentiate the model between the private sector and the public and non-profit sectors, several modifications were introduced which involve moving mission to the topmost part of the scorecard and flowing from this mission is the customer perspective. This signifies that public and non-profit organizations are customer driven while private sectors are profit driven. Basically, the objective of this project is on designing a BSC for DOST-Caraga's SET-UP Core Funded Projects. It specifically aims to review DOST-Caraga's vision and mission, assess the organization's strength, weaknesses, opportunities, and threats against the perspectives, identify stakeholder needs and identify strategies, performance objectives, measures, targets and initiatives geared towards realizing the mission. The significance of the study to DOST-Caraga is it would help the organization align its mission, vision and strategies with project results that management wants to achieve. It can imbed long-term strategy into the management system through the mechanism of measurement. The BSC solidifies the organization's focus on future success by setting objectives and performance measures from four distinct perspectives. Moreover, the scorecard provides insights of the cause-effect relationships so that resources or priorities are restructured well. It can also be used as an important quality assurance tool that can be integrated into the Quality Management System of DOST-Caraga.